Tinjauan Yuridis Perlindungan Hukum Bagi Konsumen Atas Edaran Obat yang Tidak Memiliki Izin - Ahmad Irzal Fardiansyah; Sri Riski; Khaoeirun Nissa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the legal review of legal protection for consumers related to the circulation of drugs that do not have a distribution permit in Indonesia. The research method used in this study is the normative legal research method. The main data source in this study is a secondary legal source, consisting of laws and regulations governing the circulation of drugs. The results of this study indicate that legal protection for consumers related to the circulation of drugs without a distribution permit in Indonesia has been strictly regulated in various regulations. Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 2009 concerning Health, and Regulation of the Head of BPOM Number 26 of 2017 provide a strong legal basis to ensure that drug products circulating in the market are safe and have obtained a valid distribution permit from BPOM. This aims to protect consumer rights so that they are not exposed to health risks caused by drugs that are not guaranteed to be safe. However, a major challenge faced is the high number of illegal drugs circulating, both on the black market and online platforms that are difficult to monitor. In addition, the lack of awareness from consumers also exacerbates this problem. Suboptimal supervision is also another challenge in this legal protection. The lack of utilization of technology in supervision is also a significant obstacle. Although there are regulations and supervisory authority from BPOM and pharmaceutical personnel, the distribution of drugs without a distribution permit remains a complex problem